Occurrence Of Three Alexandrium Species, A. Affine, A. Tamutum And A. Tamiyavanichii In Kuching Waters - Hii, KS; Tan, TH; Leaw, CP; Chai, HC; Takata, Y; Lim, PT (Universiti Malaysia Sarawak, (UNIMAS), 2012)
A field survey was carried out in Kuching waters to monitor harmful microalgae in Kuching waters. Samples were collected fortnightly from Semariang Batu and Santubong estuaries during high tide. Live samples were used for culture establishment, while preserved samples were processed for morphological observation under epifluorescence microscopy. The occurrence of Alexandrium affine, A. tamutum and A. tamiyavanichii is reported for the first time in the coastal waters of Sarawak, with A. tamutum as a new record in Malaysian waters, which increased the number of Alexandrium species found to eight species. They are A. affine, A. leei, A. minutum, A. peruvianum, A. tamarense, A. tamiyavanichii, A. tamutum and A. taylori. This study has provided further information to the microalgae species inventory of the country.